As propriedades temporais das orações infinitivas completivas e finais com para em Português Europeu - Silvano, Purificação; Cunha, Luís Filipe (Revista da Associação Portuguesa de Linguística, 2020)
In this paper we investigate three different types of infinitive constructions involving para in European Portuguese, viz. purpose clauses, complement clauses in which para behaves as a true complementizer and complement clauses in which para behaves as a preposition pertaining to the main sentence. We begin with a brief characterization of the Portuguese simple infinitive, arguing that, in appropriate conditions, it exhibits defective temporal properties that are, nonetheless, non-specified whenever another component in the sentence ascribes temporal information to the infinitive clause. Then we compare the three constructions under analysis: although there are clear divergences in their semantic behaviour, we observe that in all cases the situation represented by the infinitive clause is systematically located in an interval that follows its Temporal Perspective Point provided by the main clause. In order to account for this regularity, we propose that, in these contexts, (i) the infinitive is non-specified regarding its temporal features and (ii) the lexical properties of para are responsible for the posteriority reading stated above.